The North American Repository for Archaeological Isotopes - Traci N. Billings; Erin Scott; Carlo Cocozza; Sean Hixon; Nicole Boivin; Patrick Roberts; Robert N. Spengler; Ricardo Fernandes (Scientific Data)
Abstract Here, we present the North American Repository for Archaeological Isotopes (NARIA), the largest open-access compilation of previously reported isotopic measurements (n = 28,374) from bioarchaeological samples in North America (i.e., Canada, Greenland, Mexico, and the United States of America) covering a time-frame of more than 12,000 years. This database consists of stable (δ13C, δ15N, δ18O) and radiogenic (87Sr/86Sr) isotope measurements from archaeological human, animal, and plant sources and their corresponding contextual information (e.g., location, chronology, cultural affiliation, etc.). This synthesis of isotopic measurements and other forms of data presents significant research potential for investigating past human lifeways, particularly in the realms of paleomobility, paleoenvironment, and paleodiet. Additionally, it serves to pinpoint spatial and temporal data gaps, offering valuable insights for future research directions.